ANALISIS CERPEN “KADO ISTIMEWA” KARYA JUJUR PRANANTO MENGGUNAKAN PENDEKATAN OBJEKTIF - Prima Adi Bhakti; Intan Silfiani (Populer: Jurnal Penelitian Mahasiswa, 2022)
This article is a discussion of the analysis of the short story special gift by Honest Prananto which uses an objective approach, namely an approach that focuses on a literary work in a thorough and structured manner. The research method used is descriptive qualitative, namely a research method that focuses on what is thoroughly, deeply and broadly researched. By providing the results of the discussion in words and sentences as well as quality meanings without being compared with the results of other analyses. Thus the results obtained from this study are in the form of intrinsic elements: theme, point of view, plot, setting, character, character, style of language, and message from the short story special gift by Honest Prananto. It is hoped that this research can help friends in analyzing in depth the analysis of the short story A Special Gift by Honest Prananto.